Pedagogical challenge and resilience of English teachers at Islamic schools in Ajatappareng area, South Sulawesi - Fakhruddin, Zulfah - (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2020)
This study aims to find out whether there is significant difference of pedagogical challenge and resilience between English elementary, junior, and senior high school teachers or not; and to find out the correlation between teachers’ pedagogical challenge and teachers’ resilience. This study is quantitative research. Two kinds of questionnaires were administered to find out data about pedagogical challenge and resilience. Sample of this study was 84 English teachers consists 11 elementary schools teachers, 52 junior high schools teachers, and 21 senior high schools teachers. Data was analyzed by using descriptive statistic, t-test significance and Pearson correlation. The findings show that: (1) there is no significant difference of pedagogical challenges between elementary, junior, and senior Islamic school teachers, (2) there is no significant difference of resilience between elementary, junior, and senior Islamic school teachers, and (3) there is no correlation between teachers’ pedagogical challenges and teachers’ resilience.